Heterogeneous proton-coupled electron transfer in seven-coordinate iron superoxide dismutase mimetics: Concerted mechanism for two-proton one-electron transfer - Sarauli, David; van Eldik, Rudi; Ivanovic-Burmazovic, Ivana (Inorganic Reaction Mechanisms, 2012)
In this work, electrochemical studies on the seven-coordinate iron complex (Fe III/II dapsox), a functional model for the superoxide dismutase enzyme (SOD mimetic), were performed in an aqueous solution over the pH range 1 - 12 (with and without buffers) to conceive the underlying heterogeneous proton-coupled electron transfer (PCET) processes of various complex species. The thermodynamics of the corresponding proton transfer, electron transfer, and PCET processes have been evaluated as well as the kinetics of related heterogeneous electrode reactions of all complex species in solution. Measurements in D 2 O have also been carried out for selected redox couples to assess a possible kinetic isotope effect (KIE). In the case of a two-proton one-electron transfer process in the absence of a buffer, the KIE was found to be 4.8, whereas in the case of a one-proton one-electron transfer process in buffered solutions, an inverse KIE was observed. The overall data suggest the operation of a concerted PCET mechanism for the two-proton one-electron transfer process, whereas involvement of an H-bonded precursor adduct formed between the buffer components, and the complex species within a one-proton one-electron transfer mechanism is feasible. These results shed light on both the enzymatic and the mimetic SOD mechanisms, speaking in favor of the two-proton one-electron transfer process as a desirable mechanism for efficient catalytic superoxide dismutation. © 2012 Walter de Gruyter GmbH, Berlin/Boston.